ASSESSMENT OF THE EFFECTIVENESS OF USING INVECTITIS IN THE PROCESSING OF SMALL BUSINESS AND PUBLIC EDUCATION (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In the article, in the development of the national methodology for evaluating the effectiveness of the use of investments in the development of small business and private entrepreneurship, universal analytical approaches that are specific to the country's economy and can reflect the general characteristics of various sectors and branches of the republic's economy are reflected. It is recommended to divide the factors affecting the efficiency of investment activity of small business and private business entities into different groups based on the degree of mutual relationship.
Keywords: Investment potential, investment attractiveness, component approach, growth point, systematic approach, gross income, discounted net income, cash flow, payback period, endowment, internal rate of return, risk sensitivity index.